THE INTEGRATION OF HOTS-ORIENTED INSTRUCTION IN GRAMMAR CLASS - Titi Lestari; Dinar Martia Azizah (Journal of English Education, Literature and Linguistics, 2020)
Commonly, grammar is seen as a rigid, boring course, even less contributing to the improvement of the other English skills. In fact, the purpose of learning grammar is to improve the quality of communication both oral and written. In other words, the better the grammar understanding, the more likely the other skills will increase. The problem found in the field is that grammar has been taught deductively. The accompanying exercises are still in the Lower Order Thinking Skills (LOTS) realm. In fact, there are many models of activities and exercises offered by various sources (textbooks) that support the integration of Higher Order Thinking Skills (HOTS), so that grammar learning is more contextual and communicative. Therefore, other macro skills will be promoted. This study describes how HOTS-oriented instruction in grammar class is implemented and how the implementation supports the improvement of students’ macro skills. This study belongs to an Action Research. The data collection techniques include observation, interviews, and documentation. The gained data were analysed using model from Miles, Huberman, and Saldana (2014) which includes data collection, data condensation, data presentation, and drawing conclusions. The results indicate that the HOTS principles were done through employing pictures, videos, brochures as the materials and the exercises designed in various activities such as giving opinion, dialogues, writing simple stories. The HOTS integration yields promotion on students’ macro skills such as writing, reading and speaking. Their works are more meaningful and reach the level of analyzing, not only at the level of remembering and understanding.